Covalent organic framework-supported Fe–TiO2 nanoparticles as ambient-light-active photocatalysts. Issue 27 (25th June 2019) - Zhang, Yumin; Hu, Yiming; Zhao, Jianhong; Park, Eunsol; Jin, Yinghua; Liu, Qingju; Zhang, Wei
Abstract : COF-supported ultrafine crystalline Fe–TiO2 nanoparticles were prepared, which show ambient light photocatalytic activity with high efficiency, stability, and recyclability. Abstract : We have developed an efficient approach for preparation of ultrafine and well-dispersed crystalline Fe-doped TiO2 nanoparticles (Fe–TiO2 ) with a size distribution of 2.3 ± 0.9 nm under mild conditions by using covalent organic frameworks (COFs) as the interface engineering agent. The as-synthesizedFe–TiO2 @COF shows an exceptional photocatalytic activity degrading methylene blue (MB) under ambient light. A trace amount (0.4 mg) of the optimal catalyst 5Fe–TiO2 @COF can degrade MB (100 mg L −1, 4 mL) under ambient light. More importantly, the catalyst exhibits excellent stability and can be reused multiple times without any loss of catalytic activity. The use of a crystalline porous COF as a catalyst support has many unique advantages, including controlled-growth of nanoparticles with ultrafine size, stabilization of nanoparticles, efficient sorption of the organic pollutant thus increasing their local concentration around the catalysts, and facilitating the mass transfer through its porous channels. Our study provides an efficient and novel approach for preparation of well-dispersed ultrafine metal oxides with high stability and photosensitivity for energy and environmental applications.